The Rapid Escalation of Fentanyl in Illicit Drug Evidence in Allegheny County, Pennsylvania, 2010-2016. (March 2018) - Creppage, Kathleen E.; Yohannan, Joshua; Williams, Karl; Buchanich, Jeanine M.; Songer, Thomas J.; Wisniewski, Stephen R.; Fabio, Anthony
Opioid overdose deaths in the United States quadrupled from 1999 (n = 8050 deaths) to 2015 (n = 33 091 deaths), and the number of deaths associated with synthetic opioids, such as fentanyl, increased from 3105 deaths in 2013 to nearly 20 000 deaths in 2016. Given this rapid increase, timely surveillance for drugs in circulation is crucial. However, current surveillance systems used to track drug overdoses do not detect new drugs in circulation quickly. We studied the change in the presence of fentanyl in "stamp bag" drug evidence in Allegheny County, Pennsylvania, from 2010 through 2016. Stamp bags are small wax packets with individual stamps that contain mixtures of drugs, most commonly heroin, that law enforcement officers seize and retain as legal evidence. The proportion of stamp bags determined to contain fentanyl or a fentanyl analog was 2.1% in 2014 and rose sharply to 17.1% in 2016. Monitoring the chemical makeup of drug evidence items could help public health authorities identify drug use trends in their jurisdictions.